Eksistensi Asas-Asas Hukum Perjanjian Internasional Dalam Hukum Postif Dan Implementasinya Perjanjian Celah Timor - Ahmad Fadli Fauzi (Jurist-Diction, 2023)
AbstractThis study indicate that the existence of international treaty law principles has been recognized by international law subjects or the international community and is listed in the Vienna Conventions of 1969 and 1986, UU 24/2000 concerning International Agreements. The implementation of the principles of international law can be seen in the case of the Timor Gap Agreement. In the agreement previously there was an agreement involving the state of Indonesia and Australia so that the pacta sunt servanda postulate came into effect. Then, the separation of the state of Indonesia and East Timor had implications for a fundamental shift in conditions within Indonesia's territory and the entry into force of the rebus sic stantibus postulate and in the previous Timor Gap Agreement (Indonesia and Australia, 1989) did not apply to Timor Leste as a third party in accordance with the postulate of the Pact. tertiis nec nosent nec prosunt principle, because the agreement only involves Indonesia and Australia. Keywords: Interest subsidies; legitimacy of government; Directorate General of Treasury AbstrakPenelitian ini menunjukkan bahwa eksistensi asas-asas hukum perjanjian inetrnasional telah diakui oleh subjek hukum internasional atau masyarakat internasional dan tercantum dalam Vienna Conventions tahun 1969 dan 1986, Undang-Undang 24/2000 tentang dengan Perjanjian Internasional. Implementasi dalam asas-asas hukum internasional dapat dilihat pada kasus perjanjian celah timor. Dalam perjanjian tersebut sebelumnya terjadi kesepakatan yang melibatkan negara Indonesia dengan Australia sehingga berlakunya postulat pacta sunt servanda. Kemudian, dengan berpisahnya negara Indonesia dengan Timor Timur berimplikasi pada terjadinya pergeseran keadaan yang fundamental dalam wilayah Indonesia serta berlakunya postulat rebus sic stantibus dan dalam perjanjian celah timor sebelumnya (Indonesia dan Australia, 1989) tidak berlaku bagi Timor Leste sebagai pihak ketiga sesuai dengan postulat pacta tertiis nec nosent nec prosunt principle, karena dalam perjanjian tersebut hanya melibatkan Indonesia dan Australia. Kata Kunci: Subsidi Bunga; keabsahan tindakan pemerintahan; Direktorat Jenderal Perbendaharaan